An economic analysis of national economies under the CARICOM Single Market and Economy : towards a new economic geography (NEG) model - Abdulkadri, Abdullahi (2012)
Presents the findings of concluded research aimed at developing a New Economic Geography (NEG) model for the Caribbean, which will facilitate the identification and measurement of disparities and cohesion amony select regional states.